2015
DOI: 10.1111/eci.12405
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia and Morg1 in renal injury

Abstract: Background Renal hypoxia is known to play an important role in the pathophysiology of acute renal injury as well as in chronic kidney diseases. The mediators of hypoxia are the transcription factors HIF (hypoxia-inducible factors), that are highly regulated. Under normoxic conditions constitutively expressed HIF-a subunits are hydroxylated by prolyl hydroxylases (PHD1, PHD2, and PHD3) and subsequently degraded by proteasomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
(221 reference statements)
2
11
0
Order By: Relevance
“…Additionally, several studies in CKD animal models suggest that HIF-1α is suppressed by factors including oxidative stress and uremia and underlies the pathogenesis of CKD18. HIF-1α has been extensively described as a key factor for cell adaptation to hypoxia, including renal tissue19. Consistently with our previous results3 and the findings presented here, the activation of HIF-1α post-ischemia by pharmacological treatment with PHDs inhibitors significantly reduces renal I/R injury20.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, several studies in CKD animal models suggest that HIF-1α is suppressed by factors including oxidative stress and uremia and underlies the pathogenesis of CKD18. HIF-1α has been extensively described as a key factor for cell adaptation to hypoxia, including renal tissue19. Consistently with our previous results3 and the findings presented here, the activation of HIF-1α post-ischemia by pharmacological treatment with PHDs inhibitors significantly reduces renal I/R injury20.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that HIF, as a transcription factor, plays a critical role in regulating transcription of genes that promote angiogenesis, erythropoiesis, cell metabolism, cell survival and apoptosis . HIF is central to real protection in different models of kidney injury like chronic kidney disease, renal ischaemia‐reperfusion injury and nephrotoxic or ischaemic acute kidney injury . In previous studies, suppression of HIF at different levels of regulation was observed in renal cells induced by cisplatin and HIF activation attenuated apoptosis .…”
Section: Discussionsupporting
confidence: 79%
“…A wide range of pathogenesis including ischemia, hypertension, and infections could result in AKI [2], among which ischemia is known as a main leading insult that causes dysfunction of kidney [3]. Some studies reported that AKI could increase the risk of chronic kidney disease (CKD) development and end-stage renal disease (ESRD) with time.…”
Section: Introductionmentioning
confidence: 99%